Increasing the filtration characteristics of rocks in areas of high temperatures - Kovalchuk, Yuliia; Svitlytskyi, Viktor; Ivankiv, Olga; Shinkarenko, Valentin; Boshkova, Irуna (Technology audit and production reserves, 2022)
One of the important problems of the oil and gas industry is the decrease in the production characteristics of wells in fields that are at the final stage of development. In addition, the drop in well production below their potential and the decrease in hydrocarbon recovery factors are often due to the deterioration of the reservoir properties of rocks in the process of drilling in productive formations, well workover, as well as the imperfection of production processes and means of their implementation. The object of research is the technology of treatment of the bottomhole formation zone with non-acidic systems based on ammonium salts for the intensification of hydrocarbon production. The paper considers a number of methods that allow solving the above problems, taking into account their complexity, efficiency and duration of the positive effect of processing. The main acid methods of influencing the bottomhole formation zone and their modifications are analyzed. The authors, using the results of the research and experience gained, proposed a non-acidic system of chemical treatment of oil and gas wells based on ammonium salts. Their influence on the rocks occurs more long-term and does not lead to the destruction of reservoirs. During the research, physical, chemical, physicochemical methods and techniques developed by the authors for processing and analyzing field data, statistical methods for processing experimental studies were used. Modeling of deep processes was carried out on the installation developed and created by the authors. The mechanism of interaction of ammonium salt solutions with terrigenous and carbonate rocks is revealed. Experimental studies have confirmed and theoretically substantiated the effectiveness of the use of ammonium salts to improve the filtration characteristics of reservoirs. The effect of ammonium salt solutions on the change in the permeability of sandy and carbonate reservoirs in the Dnipro-Donetsk depression (DDD, Ukraine) has been studied. And also a mathematical model of the process of increasing the permeability of rocks during their dissolution by the studied chemical reagents was created. The mathematical model is available for its wide application in the practice of technological calculations and designing measures for the stimulation of oil and gas production.